BST Capacitor Thin Films - Nurjuliana, Juhari; Nur Syakimah, Ismail; Nor Zahiyah, Nordin (Malaysian Invention and Design Society (MINDS), 2010)
Nurjuliana and her team won gold at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.